STATE BODIES EXECUTING CONTROL OVER LAW ENFORCEMENT ON THE LEGAL REGULATION OF THE CONSTRUCTION OF MULTISTORY HOUSES - Ro’zmetov Navro’zbek Ikramjanovich (Scholar Express Journals, 2023)
This article describes the bodies that carry out public policy and control in the construction industry, their tasks and functions, the role of prosecutor's offices in this area, regulatory and legal foundations, problems that exist in practice today, obligations of state bodies in the examination of entrepreneurial subjects, procedures for providing guidance for verification, the procedure for examining project-estimate documents in construction
Keywords: Examination; construction control; master plan